2017
DOI: 10.1051/e3sconf/20172200149
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the AERMOD dispersion model over complex terrain with different types of meteorological data: Tracy Power Plant experiment

Abstract: Abstract. The accuracy of air pollutants dispersion modelling results depends on the quality of the input data, including the representativeness of the meteorological data. The paper presents the results of the AERMOD model validation using data from Tracy Power Plant experiment (Nevada, USA) with various meteorological data sources, including WRF modelling system outputs. The highest efficiency of the AERMOD model performance was found using site-specific meteorological data and the results from the WRF model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
(32 reference statements)
0
8
0
1
Order By: Relevance
“…A clear matrix presentation of the obtained results is particularly suitable for presenting the results of the multicriteria evaluation, which is especially important in the SEA phases with the participation of the public. However, at the level of strategic planning and management, it is not necessary, and due to the lack of appropriate inputs, it is often not possible to use different mathematical methods, such as ARAS-Additive Ratio Assessment [36], AERMOD [37], or AHP-Analytical Hierarchy Process [38], or a holistic and inclusive approach that brings together different actors and disciplines for a successful transition to a circular economy [39]. The results of the assessment in the SEA represent the basis for establishing adequate guidelines when applying these methods and some other methods at a lower hierarchical level of impact assessment, i.e., when developing EIA-Environmental Impact Assessment and ESIA (Environmental Social Impact Assessment) [40].…”
Section: Discussionmentioning
confidence: 99%
“…A clear matrix presentation of the obtained results is particularly suitable for presenting the results of the multicriteria evaluation, which is especially important in the SEA phases with the participation of the public. However, at the level of strategic planning and management, it is not necessary, and due to the lack of appropriate inputs, it is often not possible to use different mathematical methods, such as ARAS-Additive Ratio Assessment [36], AERMOD [37], or AHP-Analytical Hierarchy Process [38], or a holistic and inclusive approach that brings together different actors and disciplines for a successful transition to a circular economy [39]. The results of the assessment in the SEA represent the basis for establishing adequate guidelines when applying these methods and some other methods at a lower hierarchical level of impact assessment, i.e., when developing EIA-Environmental Impact Assessment and ESIA (Environmental Social Impact Assessment) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion models that are commonly used include the steady-state Gaussian plume, Lagrangian-based trajectory, and grid models based on grid division. Popular diffusion models comprised of AERMOD, developed by the American Meteorological Society in conjunction with US Environmental Protection Agency (USEPA) (Rzeszutek et al, 2017); industrial source…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The use of meteorological data from weather prediction models in air quality modeling (including radioactive pollutants) is therefore unavoidable on a local scale, which is confirmed by numerous studies that used data from meteorological models [21,23,35,[42][43][44][45][46][47]. On the other hand, many studies [2,5,6,48] demonstrated that the use of data from meteorological models results in decreased accuracy in predicted air pollutant concentration levels.…”
Section: Introductionmentioning
confidence: 96%
“…Spatial representativeness of the measurement data is limited. The use of meteorological data from sites located several to dozens of kilometers from the source may lead to unrepresentative results of dispersion modeling, especially in complex terrain [5,6]. Found in the literature, one of the solutions to this problem is to obtain data from an advanced meteorological model, e.g., WRF (Weather Research and Forecasting model) or MM5 (Fifth-Generation Penn State/NCAR Mescoscale Model).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation